Evaluation of Core Elements of Antimicrobial Stewardship Programs in Jordanian Hospitals - Ababneh, Mera; Issa, Noor; Alkhatatbeh, Mohammad (Jordan Journal of Pharmaceutical Sciences, 2017)
This study aimed to assess the main core elements of Antimicrobial Stewardship Programs (ASPs) in Jordanian hospitals. This was a cross sectional study in which, face-to-face interview was conducted with infectious disease physician or clinical pharmacist in infectious disease unit. Forty-one hospitals responded to the survey (response rate 68%). Among participating hospitals, 17.1% had an infectious disease physician as a leader of ASP, while 73.2% had clinical pharmacist as a leader. However, none of the hospitals had financial statement that supports ASPs duties. Clinicians were the most cooperative staff (51.2%) and microbiologists were the least cooperative staff with ASPs team (17.1%). Antibiotics preauthorization was required by 75.6% of hospitals for few broad spectrum antibiotics, 36.6% of hospitals conduct prospective audit with feedback, and 9.8% change automatically from intravenous to oral route. For tracking purposes, 19.8% of hospitals track rates of Clostridium difficle infections, and 29.3% produce antibiograms for surveillance purposes. ASPs in Jordan are in the developing phase, this demands additional support at both institutional and national levels to enable the ASPs from taking its active role.